Saudi parent's attitude and practice about self-medicating their children - Ahmed S Eldalo (Archives of Global Professionals, 2013)
Objective: The objective of this study was to test the parental self-medication attitude and practice toward their children in Saudi Arabia. Materials and Methods: A cross-sectional study was conducted. Non-probability convenient random sampling method was used to select the participants. A total of 750 parents from different cities in the Saudi Arabia were involved in the study. Results: The obtained response rate was 80%. The majority of participants were used to treat their children by western medicines. Most of respondents self-medicated their children in the month previous to the study period. The most common reported self-treated symptom was fever, although the most frequently used medicines were paracetamol and antibiotics. The attitude to treat fever was higher in males than in females (P = 0.021). The initial response for most participants in case of self treatment failure was to consult physicians in public hospitals; education level of participants showed significant difference (P = 0.041). The main reasons for self-medication were long waiting time in the clinics and high consultation fees. Occupation showed a significant differences (P = 0.008). Conclusion: The current study revealed the fact that parental self-medication among public in Saudi Arabia is a routine practice. The researchers suggested introduction of parental educational interventions throughout the Saudi Arabia to ensure that children will receive best pharmaceutical care.